ANALYSIS OF THE IMPOSITION OF CRIMINAL SANCTIONS ON PERPETRATORS OF HOMICIDE OFFENSES WITH PARANOID SCHIZOPHRENIA - Banjarnahor, Shalom Inka Nauli; Rasji (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
A person suffering from a mental disorder cannot be held criminally responsible, as stipulated in Article 44 of the Indonesian Criminal Code. However, some judges still impose criminal sentences on defendants with mental disorders. One example is Supreme Court Decision Number 1675K/Pid/2024, which concerns a murder case committed by an individual diagnosed with Paranoid Schizophrenia. This study aims to examine the legal basis and juridical considerations used by judges in rendering their verdicts, as well as to analyze how Article 44 paragraph (1) of the Indonesian Criminal Code is applied to perpetrators of murder who suffer from Paranoid Schizophrenia. The author adopts a qualitative normative legal research method, focusing on legal norms contained in legislation, court decisions, and prevailing societal norms. Based on the findings, in Supreme Court Decision Number 1675K/Pid/2024, the panel of judges applied a strict interpretation of Article 44 paragraph (1) of the Indonesian Criminal Code. Although the defendant was proven to suffer from Paranoid Schizophrenia, the judges concluded that the disorder did non entirely eliminate the defendant’s awareness or ability to be held responsible for his actions. Furthermore, the application of Article 44 paragraph (1) of the Indonesian Criminal Code to individuals with mental disorders requires careful evaluation of their mental condition based on expert psychiatric assessments. However, in judicial practice, disparities in interpretation and application of this article still occur.